(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to the problem of socialization of an individual in the process of foreign language learning, which is a part of multicultural education and is considered as an important tool for a person’s adaptation in a multicultural society. The leading idea of the article is the assertion that foreign language as a discipline has a huge socializing potential, as in the process of a foreign language learning, not only the active development of natural resources, abilities, initiative, independence, take place, but also, assimilation of generally accepted in a society socio- cultural rules and moral norms, which plays a crucial role in the process of socialization is activated. Since the main goal of the educational process in foreign languages is the formation of the very communicative skills, its contribution to the process of socialization of a man is indisputable. In this sense, the following characteristics of the learning process in a foreign language are important: the focus on communication, respect for the identity and culture of other peoples, the focus on social activities, the acquisition of social experience in solving life and social problems, and the creation of its own system of life priorities. The communicative method of teaching foreign languages is based on the fact that the learning process is a model of communication. The learning process in foreign languages is based on the linguistic partnership, creative collaboration, constant motivation of communication, based on a combination of such interconnected factors as activity, creativity, autonomy, individualization, which contribute to the intensification of cognitive and educational processes. That is, organization of training in the form of communication is the main methodological task of a modern teacher of foreign languages. It is this specificity of the discipline "foreign language" that is capable of effective implementing educational socialization, helping to complete the formation of the students’ ability to communicate, co- exist and cooperate in the professional activities of people of different ethnic groups, the formation of a rich experience of social and cultural communication, which is a solid base for the involvement of learners to the global values of civilization.